The Relationship between Online Learning and Student Achievement Levels during the Covid 19 Pandemic in Diploma Midwifery Students in Nabire Diploma Midwifery Study Program in 2022 - Ninik Indayani; Sitti Mardiana (Global Writing Academica Researching and Publishing, 2023)
The purpose of this study was to determine the relationship between online learning and student achievement levels during the Covid 19 pandemic in D3 Midwifery students at D3 Midwifery Study Program Nabire in 2022. This study used an analytic observational study with a cross sectional approach. The number of samples used in this study amounted to 200 respondents. by using chi quare analysis. The results of the analysis using the Chi-Square test obtained a value of X2 and a value of p = 0.00 <0.05 so that the results obtained were H1 accepted and H0 rejected, which means that there is a significant relationship between online learning and the achievement level of Nabire D3 Midwifery students. Statistically there is a significant relationship between online learning and student achievement levels, where student achievement levels decrease during online learning compared to face-to-face or offline learning. The conclusion of this study is that there is a relationship between online learning methods and student achievement levels. It is hoped that education can improve better learning media so that learning achievement can be maintained.